Fungsi e-KTP Untuk Mendukung Pemerintah Daerah Dalam Pendataan Dan Pelayanan Publik - Hardianto, Willy Tri; Firdausi, Firman; Lestari, Asih Widi (Universitas 17 Agustus 1945 Surabaya, 2021)
The electronic ID card program has only been launched in the last few years. This aims at the effectiveness and efficiency of public services and minimizes illegal immigrants entering the country. In its implementation, the last few years have had many unexpected obstacles, such as cases of e-ID card corruption and lack of blanks. In this research, the aim is to know directly the function of e-KTP which in its implementation is given by one person and one database. The method used is qualitative to be able to know thoroughly. The results have been seen from this study are that the e-KTP function has actually been running but has not met the expectations of the community. Income is very much needed from improving individual personal data which is summarized in the e-KTP of each resident. Making e-KTP also plays a role in the follow-up process, namely data collection. That’s a government job and the provision of public services or public services so that an accurate and credible database can be created